PARENTING PATTERNS OF MUSLIM FAMILIES WHO WORK AS RURAL LABOR IN THE SOCIAL EMOTIONAL FORMATION OF EARLY CHILDREN - Istiqlaliyah, Hulailah; Zaida, Nur Aini (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This research aims to obtain a comprehensive picture of the application of Muslim family parenting patterns in the social emotional formation of early childhood, the social and emotional development of early childhood children who are raised with Muslim family parenting who work as unskilled laborers and the impact of parental parenting on social emotional formation. early childhood. This research uses a qualitative approach with descriptive methods and in-depth interview techniques, observation and documentation. The subjects of this research were 6 Muslim families whose mothers worked as unskilled laborers and had young children. The research was carried out by the Al Iman Free School (SGAI) located in the Imanuddin Mosque Area which is located at Jl. Graha Bintaro Utama No. 11, Pondok Kacang Barat – Pondok Aren – South Tangerang City. The results of the research show: the parents studied tend to use a parenting style that is authoritative or democratic. In this parenting style, parents encourage their children to be independent but still provide limits and control over their actions and substitute parents also monitor every moment of the child's development.